Lattice Anchoring Stabilizes α-FAPbI3 Perovskite for High-Performance X-Ray Detectors - Huang, Yu‑Hua; Zou, Su‑Yan; Sheng, Cong‑Yi; Fang, Yu‑Chuang; Wang, Xu‑Dong; Wei, Wei; Li, Wen‑Guang; Kuang, Dai‑Bin (Nano-Micro Letters, 2025)
Formamidinium lead iodide (FAPbI3) perovskite exhibits an impressive X-ray absorption coefficient and a large carrier mobility-lifetime product (µτ), making it as a highly promising candidate for X-ray detection application. However, the presence of larger FA+ cation induces to an expansion of the Pb-I octahedral framework, which unfortunately affects both the stability and charge carrier mobility of the corresponding devices. To address this challenge, we develop a novel low-dimensional (HtrzT)PbI3 perovskite featuring a conjugated organic cation (1H-1,2,4-Triazole-3-thiol, HtrzT+) which matches well with the α-FAPbI3 lattices in two-dimensional plane. Benefiting from the matched lattice between (HtrzT)PbI3 and α-FAPbI3, the anchored lattice enhances the Pb-I bond strength and effectively mitigates the inherent tensile strain of the α-FAPbI3 crystal lattice. The X-ray detector based on (HtrzT)PbI3(1.0)/FAPbI3 device achieves a remarkable sensitivity up to 1.83 × 105 μC Gyair−1 cm−2, along with a low detection limit of 27.6 nGyair s−1, attributed to the release of residual stress, and the enhancement in carrier mobility-lifetime product. Furthermore, the detector exhibits outstanding stability under X-ray irradiation with tolerating doses equivalent to nearly 1.17 × 106 chest imaging doses. Highlights: 1 A lattice-anchoring strategy using low-dimensional perovskite addresses structural instability in α-formamidinium lead iodide (FAPbI3) by matching crystal lattice, mitigating residual stress and tensile strain. 2 Enhanced Pb-I bonding strength and reduced lattice strain improve structural stability and carrier mobility-lifetime product, enabling efficient charge transport. 3 Optimized X-ray detectors achieve high sensitivity (1.83 × 105 μC Gyair–1 cm–2), low detection limit (27.6 nGyair s–1), and stable performance under prolonged irradiation.